Implementation Of Temporary Admission Policy on Yachts - Inayati, Inayati; Filberto, Lucas (UI Scholars Hub, 2013)
The policies regulating yachts used by foreign tourists are Regulation of the Minister of Finance No. 140/PMK.04/2007 concerning Temporary Admission of Goods and President Regulation No. 79/2011. The research aims to analyze the implementation of Temporary Admission of yachts at Benoa Port Bali. The research incorporates a qualitative approach and qualitative data analysis technique. Qualitative data are obtained from unstructured interviews with key informants. Intrinsically, the research finds some vagueness in the policies regarding stipulations on temporary guarantee and responsibility of the guarantor. It is therefore recommended that the policies be reviewed so that the guarantor will not be burdened in case a yacht-owning tourist fails to fulfill his/her responsibility. Contextually, implementation of temporary admission policies must be supported by adequate human resources and technology to enable KPPBC (Customs and Excise Control and Service Office) to give good services and undertake close monitoring on foreign yachts entering Indonesian waters.